2021
DOI: 10.1002/acr.24537
|View full text |Cite
|
Sign up to set email alerts
|

Juvenile Spondyloarthritis in the Childhood Arthritis and Rheumatology Research Alliance Registry: High Biologic Use, Low Prevalence of HLA–B27, and Equal Sex Representation in Sacroiliitis

Abstract: Objective To describe characteristics of children with enthesitis‐related arthritis (ERA) and juvenile psoriatic arthritis (PsA) who were enrolled in the Childhood Arthritis and Rheumatology Research Alliance (CARRA) registry. Methods All children with ERA and those with juvenile PsA were identified. Demographic characteristics, clinical characteristics, and treatments were described. The children with sacroiliitis and those without sacroiliitis were compared. In the children with sacroiliitis, the first visit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 17 publications
1
7
0
Order By: Relevance
“…This non-systematic search is probably guided by the fact that the analysis is not reimbursed for patients, and is therefore essentially performed if the clinical picture can t within the ILAR classi cation criteria of the ERA-subtype of JIA (or requires the removal of exclusion criterion b in a boy over 6 years of age at disease onset). The rates found in our cohort are in fact similar to those found in populations of the ERA type [27]. Interestingly, the patients included in this cohort were generally treated in accordance with the last ACR recommendations, with intra-articular corticoids preferentially used in oligoarthritis forms, methotrexate as a rst DMARD and biotherapies as a second line of treatment (in the non-systemic forms) [4,5].…”
Section: Discussionsupporting
confidence: 81%
“…This non-systematic search is probably guided by the fact that the analysis is not reimbursed for patients, and is therefore essentially performed if the clinical picture can t within the ILAR classi cation criteria of the ERA-subtype of JIA (or requires the removal of exclusion criterion b in a boy over 6 years of age at disease onset). The rates found in our cohort are in fact similar to those found in populations of the ERA type [27]. Interestingly, the patients included in this cohort were generally treated in accordance with the last ACR recommendations, with intra-articular corticoids preferentially used in oligoarthritis forms, methotrexate as a rst DMARD and biotherapies as a second line of treatment (in the non-systemic forms) [4,5].…”
Section: Discussionsupporting
confidence: 81%
“…Of the patients who had a documented HLA antigen B27 test result, the percentage of patients who were HLA antigen B27–positive in our cohort was smaller (38%) when compared with the other cohorts. However, another study suggested the prevalence may be closer to 50% in the pediatric population ( 21 ), and a more recent study reported a similar HLA antigen B27 positivity finding of 36% ( 22 ).…”
Section: Discussionmentioning
confidence: 92%
“…Disease activity at baseline predicted functional impairment by 10 years in 60% of patients [33,35,36]. Moreover, patients with JoSpA score higher in CHAQ [32,37] and bodily pain [38,39] than other JIA categories.…”
Section: Discussionmentioning
confidence: 99%